Association of Fontan Pathophysiology With Plasma Bile Acids - Ashish H. Shah, MD, MD-Research; Arun Surendran, MSc; Pedram Hassan-Tash, BSc, MD; C. Nolan Turnbull, BSc; Nicole Johnston, MSc; David Goodlett, BSc, PhD; Jun Han, PhD; Robin A. Ducas, MD; James W. Tam, MD; Eberhard Renner, MD; Todd A. Duhamel, PhD; Michel Aliani, MSc, PhD; et al. (JACC: Advances)
Background: Patients with Fontan circulation are frail and experience multisystem dysfunction including impaired exercise capacity, low resting and exercise-augmented cardiac output, and progressive liver fibrosis. However, common underlying biochemical abnormalities or disease-specific biomarkers have not been well-described. Objectives: We wish to investigate Fontan and their matched healthy subjects using a nontargeted, followed by targeted metabolomic analysis. Methods: Patients with Fontan circulation were compared to age- and sex-matched healthy controls with regard to body composition, markers of frailty, cardiopulmonary exercise testing, and resting and exercise-augmented hemodynamics. Subsequently, the study participants underwent a nontargeted metabolomics assessment, followed by targeted plasma bile acid (BA) analysis. Results: Twenty Fontan patients (28.8 ± 9.8 years of age; 35% women) and 20 healthy controls (29.7 ± 6.0 years of age; 30% women) were enrolled. Fontan patients had significantly lower skeletal muscle mass, took longer to complete the 5 times sit-to-stand test; achieved lower %VO2 max, and had lower resting and postexercise hemodynamic parameters. Nontargeted metabolomics assessment demonstrated elevated BAs, oxylipins, and leucine metabolites in Fontan patients. Total BA as well as 17 BA components were markedly elevated in the Fontan patients. Selective BAs were negatively associated with age, degree of frailty, cardiopulmonary function, and hemodynamic parameters. Conclusions: Elevated BAs are associated with worsening Fontan physiology. These findings warrant further exploration.